2022
DOI: 10.3389/fonc.2022.866542
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for Five to Fifteen Brain Metastases: A Single Centre Experience and a Review of the Literature

Abstract: PurposeStereotactic radiosurgery (SRS) is now mainstream for patients with 1-4 brain metastases however the management of patients with 5 or more brain metastases remains controversial. Our aim was to evaluate the clinical outcomes of patients with 5 or more brain metastases and to compare with published series as a benchmarking exercise.MethodsPatients with 5 or more brain metastases treated with a single isocentre dynamic conformal arc technique on a radiosurgery linac were identified from the institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In the report of CK including 233 brain metastases in 97 patients, toxicities ≥ grade 3 was not observed [20] . Also, in the report from MBM for 5–15 brain metastases, there was no toxicities ≥ grade 3 [18] . Our results suggested that MBM has steeper dose distribution, but both are considered to be equivalent in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the report of CK including 233 brain metastases in 97 patients, toxicities ≥ grade 3 was not observed [20] . Also, in the report from MBM for 5–15 brain metastases, there was no toxicities ≥ grade 3 [18] . Our results suggested that MBM has steeper dose distribution, but both are considered to be equivalent in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…These techniques achieve favorable dose distribution [13] , [14] , [15] , [16] , [17] . Also, Rogers et al reported favorable results of MBM that local control was 100 % and 99.8 % for patients with 5–9 brain metastases and 10–15 brain metastases [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS) is increasingly used for brain metastases [1][2][3] due to improved technology and emergence of single-isocenter SRS solutions in recent years. The dosimetric results of linac-based SRS are comparable to those with cyberknife (CK) and gamma-knife [4][5][6] and multiple brain metastases (MBM) as small as a few millimeters can be targeted.…”
Section: Introductionmentioning
confidence: 99%